Implementasi Pembelajaran Kooperatif Berbasis Game Class of Champions dari Platform Ruang Guru untuk Meningkatkan Hasil Belajar Perkalian Siswa SDN 067240 Medan Tembung - Lipur Ju Priman Zega; Zainal Azis; Darmawati Darmawati (Lembaga Yasin AlSys, 2025)
This study is motivated by the low Mathematics learning outcomes of elementary school students, particularly in multiplication, which are attributed to monotonous teaching methods and limited active participation. The research aims to improve the Mathematics achievement of Grade V students at SDN 067240 through the implementation of the cooperative learning model Class of Champions from the Ruang Guru platform. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model in two cycles, each comprising the stages of planning, action, observation, and reflection. The research subjects were 16 Grade V students, while the object of the study was learning outcomes measured through pretests and posttests in each cycle. The results show a significant improvement from cycle I to cycle II, with the average student score increasing from 61.25 in the pretest to 73.125 in cycle I, and 86.25 in cycle II. The percentage of students meeting the Minimum Mastery Criteria (Kriteria Ketuntasan Minimal, KKM) rose from 50% to 75% and finally to 93%. These findings demonstrate that using game-based learning media not only improves learning outcomes but also creates an enjoyable, interactive atmosphere that motivates students to engage actively. This research contributes to the development of innovative teaching strategies in elementary schools and provides a foundation for further studies on strengthening numeracy literacy through educational digital media.